Nitrogen-phosphorus relationships in lichens - Hogan, Erika (2009)
Nitrogen enrichment promotes phosphomonoesterase (PME) activity in the common heathland lichen Cladonia portentosa. This is associated with a marked increase in thallus N:P mass ratio and significant up-regulation of inorganic phosphate uptake capacity, evidencing a shift from N-limited to P-limited growth. Phosphomonoesterase activity in C. portentosa responds rapidly to change in N deposition load, with a significant increase in activity recorded within 6 months of transplantation from a low-N to high-N site. The location of PME activity in C. portentosa was revealed using a fluorescent marker and was found to be concentrated on both the outer and inner surfaces of the hollow ‘tube-like’ thallus branches. Activity appeared to be associated exclusively with the mycobiont and was located within the hyphal-lumina, consistent with a membrane bound ecto-enzyme. High PME activity in axenic mycobiont cultures of C. portentosa provided further evidence of a fungal location and confirmed that rates of activity in this lichen are amongst the highest reported for any other plant/fungal system in the literature. Different classes of phosphatases were assayed in a range of N2-fixing and non-N2-fixing lichens in an oligotrophic subarctic environment. No relationship was found between the capacities for nitrogenase and PME activities. Maximum rates of PME activity were recorded in fruticose mat-forming lichens which capture nutrients predominantly from atmospheric deposits. 5´ nucleotide phosphodiesterase activity was readily detected in N2-fixing lichens and was particularly high in rhizine-rich regions of foliose terricolous lichen thalli, consistent with the utilisation of organic phosphates from soil and litter sources.